Expulsion and Diaspora Formation Religious and Ethnic Identities in Flux from Antiquity to the Seventeenth Century - Tolan, John (Religion and Law in Medieval Christian and Muslim Societies, 2015)
The eleven essays brought together in this volume explore the relations between expulsion, diaspora, and exile between Late Antiquity and the seventeenth century. The essays range from Hellenistic Egypt to seventeenth-century Hungary and involve expulsion and migration of Jews, Muslims and Protestants. The common goal of these essays is to shed light on a certain number of issues: first, to try to understand the dynamics of expulsion, in particular its social and political causes; second, to examine how expelled communities integrate (or not) into their new host societies; and finally, to understand how the experiences of expulsion and exile are made into founding myths that establish (or attempt to establish) group identities.